2012
DOI: 10.1074/jbc.m111.329730
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the dRP/AP Lyase of Ku Promotes Nonhomologous End Joining (NHEJ) Fidelity at Damaged Ends

Abstract: Background: Ku has a 5Ј-dRP/AP lyase activity that excises abasic sites near double-strand break ends. Results: Ku excises only those abasic sites that would otherwise interfere with ligation. Conclusion: This substrate specificity promotes NHEJ fidelity. Significance: Tight control of damage excision is essential to nonhomologous end joining because this pathway typically cannot accurately replace excised DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…The AP sites near the 5′ end, which are not deeply embedded into duplex part of DNA, were considered to be relevant for direct NHEJ. Ku did not possess the AP lyase activity when an AP site was embedded in the duplex part of DNA for more than 3 bp [25]. This observation is in agreement with our results [13].…”
Section: Ku Interaction With Ap Sitessupporting
confidence: 93%
See 3 more Smart Citations
“…The AP sites near the 5′ end, which are not deeply embedded into duplex part of DNA, were considered to be relevant for direct NHEJ. Ku did not possess the AP lyase activity when an AP site was embedded in the duplex part of DNA for more than 3 bp [25]. This observation is in agreement with our results [13].…”
Section: Ku Interaction With Ap Sitessupporting
confidence: 93%
“…At the same time, it has been found that the lysine(s) of Ku80 can substitute for the mutated lysines of Ku70 with only partial decrease in the Ku activity on the AP site in the 5′ overhang [24,25].…”
Section: Ku Interaction With Ap Sitesmentioning
confidence: 98%
See 2 more Smart Citations
“…Even Pol4 activity, recruited to double-strand break ends by NHEJ core factors, is dispensable for 5 0 -dRP removal during joining in Saccharomyces cerevisiae [Daley and Wilson, 2008]. Our group's study indicates that this function is replaced during NHEJ by a 5 0 -dRP/AP lyase activity resident in the NHEJ factor Ku [Roberts et al, 2010], and which has a substrate specificity reciprocal to Pol X members; Ku is active in excising abasic sites only when they are within 4 bp of a double-strand break terminus [Strande et al, 2012].…”
Section: Catalytic Domainmentioning
confidence: 85%